1996
DOI: 10.1096/fasebj.10.10.8751721
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of interleukin‐1β‐converting enzyme in apoptosis of bFGF‐deprived murine aortic endothelial cells

Abstract: Apoptosis (programmed cell death) is an essential physiological process that is genetically regulated and contributes to the balance between cell growth, differentiation, and the maintenance of normal cells. Recent studies show that deprivation of growth factor induces apoptosis in endothelial cells. However, the molecular mechanisms regulating apoptosis remain unclear. In this study, we demonstrate that deprivation of basic fibroblast growth factor (bFGF) increased the expression of interleukin-1 beta-convert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…34 Subsequent investigations have can initiate events leading to its own death via apoptosis. [1][2][3][4][5] shown that the caspase inhibitor acetyl-YVAD-chloromethyl Apoptosis is an active form of cell suicide that is characterized ketone (Ac-YVAD-CMK) inhibits the kinetics of cell death and by cell shrinkage, membrane blebbing, chromatin conden-DNA fragmentation in CP-treated malignant glioma cells 35 or sation, and DNA fragmentation. [6][7][8] Although these hallmark VP-16-treated HL-60 cells, 36 and benzyloxycarbonyl-VADfeatures are commonly observed in drug-induced apoptosis, fluoromethyl ketone (Z-VAD-FMK) inhibits the rate of cell relatively little is known about the signaling pathways which death in VP-16-treated THP.1 human monocytic cells.…”
Section: The Treatment Of Cells With Chemotherapeutic Agents Results Inmentioning
confidence: 99%
See 3 more Smart Citations
“…34 Subsequent investigations have can initiate events leading to its own death via apoptosis. [1][2][3][4][5] shown that the caspase inhibitor acetyl-YVAD-chloromethyl Apoptosis is an active form of cell suicide that is characterized ketone (Ac-YVAD-CMK) inhibits the kinetics of cell death and by cell shrinkage, membrane blebbing, chromatin conden-DNA fragmentation in CP-treated malignant glioma cells 35 or sation, and DNA fragmentation. [6][7][8] Although these hallmark VP-16-treated HL-60 cells, 36 and benzyloxycarbonyl-VADfeatures are commonly observed in drug-induced apoptosis, fluoromethyl ketone (Z-VAD-FMK) inhibits the rate of cell relatively little is known about the signaling pathways which death in VP-16-treated THP.1 human monocytic cells.…”
Section: The Treatment Of Cells With Chemotherapeutic Agents Results Inmentioning
confidence: 99%
“…For our experiments, cells were treated with 20 M VP-16 for 6 h, followed by preparation of cytosolic extracts. The extracts were then assayed for their ability to cleave in vitro translated 35 S-PARP into characteristic fragments of 85 and 24 kDa. As shown in Figure 2, extracts from Vector cells efficiently cleaved 35 S-PARP protein (lanes 2 and 4).…”
Section: The Treatment Of Cells With Chemotherapeutic Agents Results Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Human glioblastoma U87-MG (wild-type p53, Kondo et al, 1996) and U251-MG cells (mutant p53, Van Meir et al, 1994) were used in this study. Tumor cells were cultured in Dulbecco's modi®ed Eagle's medium (GIBCO BRL, Grand Island, NY) supplemented with 10% heat-inactivated fetal calf serum (GIBCO BRL), 4 mM glutamine, 50 U/ml penicillin and 50 mg/ml streptomycin.…”
Section: Tumor Cellsmentioning
confidence: 99%